2015
DOI: 10.4141/cjps-2014-184
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different water and nitrogen levels on yield, water and nitrogen utilization efficiencies of spinach (Spinacia oleraceaL.)

Abstract: L. 2015. The effects of different water and nitrogen levels on yield, water and nitrogen utilization efficiencies of spinach (Spinacia oleracea L.). Can. J. Plant Sci. 95: 671Á679. Water and nitrogen (N) are important factors that affect crop yield. The objective of this study was to explore the interactive effect of water and nitrogen on biomass production, yield and growth responses, water and nitrogen use efficiency of winter-grown spinach. A field experiment was grown with treatments of varying water (W) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 36 publications
6
4
1
Order By: Relevance
“…Similar to this, Ref. [35] reported that spinach plants grew taller after receiving nitrogen fertilizer application.…”
Section: Plant Heightsupporting
confidence: 71%
“…Similar to this, Ref. [35] reported that spinach plants grew taller after receiving nitrogen fertilizer application.…”
Section: Plant Heightsupporting
confidence: 71%
“…The yield rose with the increase in the nitrogen dose. These results agree with those obtained on wild rocket [26] and other leafy vegetables [27][28][29]. Azo+ has made a significant contribution to increasing the marketable yield.…”
Section: Effect Of Preharvest Treatments On Rocket's Characteristics During the Shelf-lifesupporting
confidence: 90%
“…Our work indicates that the yield increasing effect of N fertilizer has a significant critical threshold, and growth inhibition will occur if that critical threshold is exceeded. N fertilizer is one of the key factors limiting the growth of crops, and both N deficiency (Van der Velde et al, 2014) and excessive (Zhang et al, 2015) application will affect the yield of crops. An appropriate nutrient supply can effectively improve the number of tillers per plant and plant height of forage, which can promote the growth and development of crops and increase yields .…”
Section: Effect Of N P and K Fertilizer Interactions On Dry Matter Biomassmentioning
confidence: 99%